Lewis and Clark Centennial March - E.A. Barnes::::::::: (Wright's Music House)
Piano score, 5 p. Score c1902 by Wrights Music Store. Cover title: Lewis and Clarke centennial march. On cover are ports. of Lewis and Clark and a birds-eye view of Portland in 1905.